ANÁLISE DA EVOLUÇÃO DO EMPREGO FORMAL DO MUNICIPIO DE PANAMBI - Pacheco, Jussiano R.; Arruda, Jônatas; Lucca, Emerson J.; Kohler, Romualdo; Trennepohl, Dilson; Schiavo, Andressa (Salão do Conhecimento, 2013)
Resumo